Potential mitigation of environmental impacts of intensive plum production in southeast China with maintenance of high yields: Evaluation using life cycle assessment - Yan, Xiaojun; Ye, Delian; Tang, Yafu; Muneer, Muhammad Atif; Christie, Peter; Tou, Congyue; Xu, Weidong; Shen, Bingrong; Xu, Jinxian; Zhang, Jiangzhou (Frontiers in Plant Science, 2023)
Intensive plum production usually involves high yields but also high environmental costs due to excessive fertilizer inputs. Quantitative analysis of the environmental effects of plum production is thereby required in the development of optimum strategies to promote sustainable fruit production. We collected survey questionnaires from 254 plum production farms in Zhao’an county, Fujian province, east China to assess the environmental impacts by life cycle assessment (LCA) methodology. The farms were categorized into four groups based on yield and environmental impacts, i.e., LL (low yield and low environmental impact), LH (low yield but high environmental impact), HL (high yield but low environmental impact), and HH (high yield and high environmental impact). The environmental impacts, i.e., average energy depletion, global warming, acidification, and eutrophication potential in plum production were 18.2 GJ ha-1, 3.63 t CO2 eq ha-1, 42.2 kg SO2 eq ha-1, and 25.1 kg PO4 eq ha-1, respectively. Only 19.7% of farmers were in the HL group, with 13.3% in the HH group, 39.0% in LL, and 28.0% LH. Plum yields of the HL group were 109-114% higher than the overall mean value of all 254 farms. HL farms showed, on a per tonne of plum production basis, lower energy depletion, global warming, acidification, and eutrophication potentials of 75.4%, 75.0%, 75.6%, and 75.8%, respectively. Overall, the total environmental impact index of LL, LH, HL, and HH groups were 0.26, 0.42, 0.06, and 0.21, respectively. Excessive fertilizer N application was the main source of the environmental impacts, with the potential to reduce fertilizer N rate based on the HL group by 34.8% compared with current practice without lowering the production output. The results provide an important basis for improved management of plum production with reduced environmental impacts for ‘green’ agricultural development.